(untitled) (Global Journal of Science Frontier Research, 2017)
The diversity and ecological importance of insects makes them very valuable for studies of biodiversity. Insects play a huge role inlives of man. Survey of Insect Biodiversity are undertaken to find out the organisms exist in a given area. The survey was carried out in Mahapoli village for the study of the ecological significance of the Insects. Insects may be found in nearly all environments, although only a small number of species reside in the oceans, a habitat dominated by another arthropod group, crustaceans. Insect bring both joy and sorrow. Their importance to human welfare transcends the grand battles. Most of us hate them, but some of us love them. Indeed at times they even inspire us. It is necessary to protect them.